Resveratrol – pills to replace a healthy diet? - Chachay, Veronique S (Blackwell Science Inc, 2011)
Nutrapharmacology, or the use of bioactive food compounds at pharmacological doses is emerging as a therapeutic approach to target the complex metabolic dysregulations in ageing and obesity-related chronic disease. Resveratrol, a polyphenol found in the skin of grapes, and other edible plants and related food products, has received extensive attention through the link with the French paradox, and later with its chemopreventive activity demonstrated in vitro and in animal cancer models. A plethora of laboratory investigations has provided evidence for the multi-faceted properties of resveratrol and suggests that resveratrol may target ageing and obesity-related chronic disease by regulating inflammation and oxidative stress. A number of obstacles stand in the path to clinical usage however, not least the lack of clinical evidence to date, and the myriad of doses and formulations available. Further, data on the effects of resveratrol consumption in a capsule vs. food form is conflicting, and there are uncertain effects of long term dosing. The review will summarize the human pharmacokinetic and pharmacodynamic published data, and the topics for research if resveratrol is to become a multi-target therapeutic agent addressing chronic disease.